Armenia Power Sector Policy Note - World Bank (Washington, DC, 2015)
The objective of the note is to inform the governments policy thinking by identifying the principal challenges that the power sector faces and outlining solutions for overcoming them. The note also discusses some broader energy sector issues related to the gas tariff structure and demand. The note will also be disseminated to increase understanding and awareness among key stakeholders and the general public on the key challenges facing the power sector and the potential solutions for overcoming them. This will help to promote improved dialogue and collaboration between the government and the other key stakeholders. The note is organized in following topics: power sector structure; synopsis of challenges and solutions; principal challenges and solutions; and annexes.